Geosynthetic as a strengthening material for brick masonry wall. (2021) - Behera, Biplab; Khan, Hasim Ali; Nanda, Radhikesh Prasad
Abstract: Geosynthetic products have been utilized widely in numerous Civil Engineering construction. The paper presents performances of in-plane shear for brick masonry panels strengthened with two varieties of geosynthetics. The walls were strengthened with geotextile surface wrapping using epoxy resins and geogrid reinforcement at the bed joints embedded in brick mortar. These panels were subjected to a diagonal compression test for determined the in-plane shear strength. From this study,  it had been determined that the load-carrying capability can be increased with the strengthening of geotextile and geogrid, stiffness, displacement capability, with respect to the un-strengthen wall. It was also observed that the shear strength under diagonal loading and in-plane strength increased both for surface wrapping and bed joint reinforcement. Furthermore, an increase in in-plane shear strength was more in case of geogrid reinforcement (43%), than surface reinforcement (29%), when compared to unstrengthened walls. The economy index showing a low-cost technique for strength enhancement of brick walls in earthquake-prone areas.